Leukemoid like reaction in a post CABG patient - G Padmakumar; J Ravikrishnan; P Jayakumar; K Prasad (Indian Journal of Anaesthesia, 2014)
The presentation of leukemoid reaction in patients post-cardiac surgery is rare with limited prior reports in the English language literature. We report a case of raised leukocyte count with no evidence of infection in a patient post coronary artery bypass graft surgery. The exaggerated inflammatory response by the patient to extra-corporeal circulation was drastically elevated, but fell short of the leukaemoid reaction definition - so we have defined it as a leukaemoid like reaction. A clear correlation between the extra-corporeal circulation and inflammatory response is documented.